Using online tools to develop conscious oral care habits in young adults - Anetta Fehér; Edit Magdolna Biró (Hungarian Dental Association, 2023)
Introduction: Online tools offer many opportunities for oral health promotion. Pre-recorded videos and reminder messages can be important complementary tools to treatments. The research aimed to assess and improve young adults' oral hygiene knowledge, habits and self-efficacy in a longitudinal study with an experimental group (EG) and a control group (CG). Patients and methods: The study was conducted over a six-week period, and at the first data collection (T0) a selfdeveloped online test package was completed, which included the Oral Hygiene Habits Scale (OHHS), the Dental Education Scale (DES) and the Self-Efficacy Scale (SES), in addition to basic sociodemographic and introductory questions. After completing the test package an informational video was presented and the DES was completed again (T1). Participants were randomly allocated into two groups, with members of the CG receiving no emails during the 6-week period and members of the EG receiving emails containing video clips and infographics twice a week. At the last data collection (T2), both groups were reassessed using the OHHS, DES and SES scales. Results: 70 participants started the study at T0, but after dropout due to the longitudinal nature of the study 50 participants completed the questionnaires at time T2, 27 from CG and 23 from EG. The criteria for inclusion in the sample were age between 18-35 years and regular follow-up of emails. The mean age of participants was 28.24 years (SD: ±3.98). DES showed a significant improvement comparing T0-T1 (CG: p < 0.001; EG: p = 0.002) and T0-T2 (CG and EG: p < 0.001) time points but there was no significant difference between T1 and T2 in either group, and no significant difference between groups at T2. For the OHHS, only the EG showed a significant difference between T0 and T2 (p = 0.010), the same result was obtained regarding the SES (p = 0.028). Discussion: A complex video material may be an effective form to give information to the patients. Our results demonstrate that one information session may be sufficient to improve knowledge levels, but repeated motivational email messages are important to change oral hygiene habits and increase self-efficacy.